The Benefits of Advance Booking Discount Programs: Model and Analysis - Tang, Christopher S.; Rajaram, Kumar; Alptekinoğlu, Aydın; Ou, Jihong (Management Science, 2004)
Consider a retailer who sells perishable seasonal products with uncertain demand. Due to the short sales season and long replenishment lead times associated with such products, the retailer is unable to update demand forecasts by using actual sales data generated from the early part of the season and to respond by replenishing stocks during the season. To overcome this limitation, we examine the case in which the retailer develops a program called the “advance booking discount” (ABD) program that entices customers to commit to their orders at a discount price prior to the selling season. The time between placement and fulfillment of these precommitted orders provides an opportunity for the retailer to update demand forecasts by utilizing information generated from the precommitted orders and to respond by placing a cost-effective order at the beginning of the selling season. In this paper, we evaluate the benefits of the ABD program and characterize the optimal discount price that maximizes the retailer’s expected profit.